The mask of Maliban - Abbott, Tony, 1952-; Jessell, Tim.; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 2001)
Prince Maliban is the creepy ruler of the Turtle City. And Maliban's mysterious mask maker, Hob, is crafting an awesome new mask. The mask is very cool but very powerful. So Eric, Neal, and Julie have to make sure the mask doesn't fall into the wrong hands. Otherwise, it could mean serious trouble for Droon.
"A Little Apple paperback."
G2
Keywords: Fantasy; Fantasy fiction